Damage of Cryopreserved Bioobjects in the Process of Cluster Crystallization of Cryoprotective Solutions - Sevastianov, Stanislav S.; Osetsky, Aleksandr I. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â  Probl Cryobiol Cryomed 2014; 24(2):165.